Nghiên cứu phân hủy thuốc bảo vệ thực vật, đã hết hạn sử dụng bằng xúc tác phức của Co(II) với axetylaxeton - Huỳnh, Lê Văn; Thủy, Trương Thị; Hà, Trần Thị (Vietnam Journal of Chemistry, 2016)
The living environment is severely contaminated by the toxic wastes discharged into the environment, which polluted land, water and air environments. The waste is a direct threat to human living environment, as well as living organisms on Earth. There have been many methods are to handle the hazardous waste such as: Processing of domestic wastewater, industrial wastewater, process waste gas and solid waste. Especially the handling of plant protection drugs used in agriculture has expired is extremely difficulties, requiring the cost of handling very expensive. This paper presents the result of applied research, catalysis, complex, created by ion Co(II) with Axetylaxeton (Acac), to the destruction of pesticide DDT (dichloro-diphenyl-trichloroethane) has expired use duration, must be destroyed. The results DDT the destruction of time 120 minutes achieved 90.4 % performance. The obtained results are the scientific basis for the use of catalytic complex [Co(Acac)]+ in the production process technology. Keywords. Handling of plant protection drugs, pollution, waste discharge, environment.